Inhibitory effects of propofol on Th17 cell differentiation. (4th July 2017) - Lin, Chi-Chien; Chen, Der-Yuan; Tang, Kuo-Tung; Chao, Ya-Hsuan; Shen, Ching-Hui; Lui, Ping-Wing
Abstract: Propofol (2, 6-diisopropylphenol) is probably the most widely used intravenous anesthetic agent in daily practice. It has been reported to show immunomodulatory activity. However, the effect of propofol on the differention of T cells remains unclear. In this study, we demonstrated for the first time that propofol inhibited both interleukin (IL)-6 plus transforming growth factor-β (TGF-β)-induced Th17 cell differentiation in vitro and in LPS-challenged mice. Propofol also suppressed the IL-6-induced phosphorylation of Janus kinase-2 (JAK2)/signal transducer and activator of transcription (STAT3) pathway, a cytokine-activated essential transcription factor in Th17 cell development, which occurred concomitantly with the enhancement of suppressor of cytokine signaling-3 (SOCS3) expression involved in the downregulation of STAT3 phosphorylation. These data extend our knowledge of the immunosuppressive effects of propofol and their underlying mechanism.